Tissue micro array analysis of ganglioside N-glycolyl GM3 expression and signal transducer and activator of transcription (STAT)-3 activation in relation to dendritic cell infiltration and microvessel density in non-small cell lung cancer - van Cruijsen, Hester; Ruiz, Mariëlle Gallegos; van der Valk, Paul; de Gruijl, Tanja D; Giaccone, Giuseppe (BMC cancer, 2009)
Background Tumor immune escape and angiogenesis contribute to tumor progression, and gangliosides and activation of signal transducer and activator of transcription (STAT)-3 are implicated in these processes. As both are considered as novel therapeutic targets, we assessed the possible association of ganglioside GM3 expression and STAT3 activation with suppression of dendritic cell (DC) activation and angiogenesis in non-small cell lung cancer (NSCLC). Methods Immunohistochemistry was performed on a tissue array to determine N -glycolyl GM3 (GM3) and phosphorylated STAT3 (pSTAT3) expression in 176 primary NSCLC resections. Median values of GM3 and pSTAT3 expression were used as cut off. Microvessel density (MVD) was determined by CD34 staining and morphology. CD1a and CD83 were used to determine infiltrating immature and mature dendritic cells, respectively. Results 94% and 71% of the NSCLC samples expressed GM3 and nuclear pSTAT3, respectively. Median overall survival was 40.0 months. Both low GM3 expression and high pSTAT3 expression were associated with a worse survival, which reached near significance for GM3 ( P = 0.08). Microvessel density (MVD), determined by CD34 staining and morphology, was lower in NSCLC samples with high GM3 expression. CD1a + cells (immature DCs) were more frequent in NSCLC tissues as compared to peritumoral lung tissue, while CD83 + cells (mature DCs) were more frequent in peritumoral lung tissue. CD83 + DCs were less frequent in NSCLC tissues with high GM3 expression. Conclusion GM3 and pSTAT3 are widely expressed in NSCLC. Based on CD83 expression, GM3, but not pSTAT3, appeared to be involved in tumor-induced DC suppression. pSTAT3 expression was not associated with MVD, while GM3 might play an anti-angiogenic role.